2016
DOI: 10.1016/j.molp.2015.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis NRT1.5 Mediates the Suppression of Nitrate Starvation-Induced Leaf Senescence by Modulating Foliar Potassium Level

Abstract: Nitrogen deficiency induces leaf senescence. However, whether or how nitrate might affect this process remains to be investigated. Here, we report an interesting finding that nitrate-instead of nitrogen-starvation induced early leaf senescence in nrt1.5 mutant, and present genetic and physiological data demonstrating that nitrate starvation-induced leaf senescence is suppressed by NRT1.5. NRT1.5 suppresses the senescence process dependent on its function from roots, but not the nitrate transport function. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(62 citation statements)
references
References 66 publications
1
60
0
1
Order By: Relevance
“…Leaves and roots were harvested and washed at least three times by ultrapure water for 5 min and then extracted nitrate as described 56 .…”
Section: Methodsmentioning
confidence: 99%
“…Leaves and roots were harvested and washed at least three times by ultrapure water for 5 min and then extracted nitrate as described 56 .…”
Section: Methodsmentioning
confidence: 99%
“…The Sensitive Phenotype of lks2 Depends on Low K + Previous reports have observed that K + transport in the nrt1.5 mutant was reduced (Lin et al, 2008;Drechsler et al, 2015;Meng et al, 2016), and this reduction was dependent on NO 3 2 (Lin et al, 2008). Our results here showed that there was no obvious phenotypic difference between wild-type and mutant plants when grown on high K + (5 mM) medium, although the NO 3 2 concentration in the medium was decreased from 5 to 0.1 mM ( Figure 3A; Supplemental Figure 5C).…”
Section: K + and Nomentioning
confidence: 96%
“…Thus, NRT1.5, which belongs to a family that includes several NO 3 − transporters, was initially characterized as a transporter involved in NO 3 − release into the xylem (Lin et al ). However, it has recently been shown that this transporter also mediates K + release into the xylem and coordinates K + /NO 3 − distribution in plants (Drechsler et al , Meng et al , Li et al ).…”
Section: Signaling Of K+ and No3− Po43− And So42− Deficienciesmentioning
confidence: 99%
“…Plant. 165,2019 recently been shown that this transporter also mediates K + release into the xylem and coordinates K + /NO 3 − distribution in plants (Drechsler et al 2015, Meng et al 2016, Li et al 2017).…”
Section: Related Tomentioning
confidence: 99%